(untitled) (American Journal of Society and Law, 2025)
The refusal of Jehovah’s Witnesses patients to receive blood transfusions poses a normative conflict between several human rights. On one hand, there is the “Right to Religious Freedom”, which allows these patients to rely on their religious convictions to refuse such medical procedures. On the other hand, there are the “Right to Life” and the “Right to Health”, which obligate healthcare professionals to perform all necessary actions to preserve patients’ lives and improve their health. Additionally, healthcare professionals are bound by the commitments and guidelines of their profession in performing their duties. Within this context, the current study conducts a qualitative analysis of articles, legal instruments, and ethical frameworks. The study employs a legal analysis to explore the normative conflict surrounding blood transfusions for Jehovah’s Witness patients in Spain. It focuses on the interplay between the Right to Religious Freedom, Right to Life, and Right to Health using a qualitative approach. The analysis considers relevant legal instruments, ethical frameworks, and case law to identify critical factors influencing decision-making in medical practice, particularly the patient’s state of consciousness and the urgency of their condition. It concludes that the patient’s state of consciousness and the severity of their condition are the decisive factors. If the patient is conscious and not in a critical condition, their decision to refuse the treatment should take preeminence. Conversely, in cases where a blood transfusion is necessary but not urgent, the matter should be brought before the competent judicial bodies for a decision. However, in situations where the transfusion is both necessary and urgent to save the patient’s life, the decision will be made by the healthcare professionals involved, who must then assume the consequences of their actions.